Teachers' Perspectives on Boys' Underperformance in Education in Khyber Pakhtunkhwa, Pakistan - Raza Ullah; Hazir Ullah (University of Maribor Press, 2021)
This article is an attempt to explore possible causes of boys' underperformance in the Secondary School Certificate (SSC) and Higher Secondary School Certificate (HSSC) Annual examinations of the Board of Intermediate and Secondary Education (BISE) Peshawar, KP, Pakistan. The aim of the study is to explore the issue of boys' underperformance from the perspectives of school and college teachers. Thus, the data for the study come from qualitative interviews with 30 school and college teachers (15 male and 15 female). We employed purposive sampling technique for including teachers. The findings of the study recommend that evidence-based strategies need to be adopted to improve boys' academic performance and attitudes to learning.